2008
DOI: 10.1002/anie.200704293
|View full text |Cite
|
Sign up to set email alerts
|

A Catalytic Aldol Reaction and Condensation through In Situ Boron “Ate” Complex Enolate Generation in Water

Abstract: Cooperation is key: N‐Butyl‐1‐benzimidazole‐2‐phenylboronic acid hydroxide complex catalyzes the aldol condensation and aldol addition between hydroxyacetone or acetone, and different aldehydes in water. The catalytic activity results from cooperative interactions between the boronate complex and the imidazole function. Aldol condensation gives the unsaturated methyl ketones of acetone, whereas aldol addition predominates with hydroxyacetone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…In the first, a straightforward 1,3‐dipolar cycloaddition of metalloazomethine ylide intermediate B to aldehyde would lead directly to oxazolidine product C (pathway A). Alternatively, ylide B could participate in an aldol‐type reaction to produce intermediate 19 , which could then cyclize to oxazolidine product C (pathway B) 3741. Imine 14 (R 1 = H) is believed to participate in a 1,3‐dipolar cycloaddition with the aryl aldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…In the first, a straightforward 1,3‐dipolar cycloaddition of metalloazomethine ylide intermediate B to aldehyde would lead directly to oxazolidine product C (pathway A). Alternatively, ylide B could participate in an aldol‐type reaction to produce intermediate 19 , which could then cyclize to oxazolidine product C (pathway B) 3741. Imine 14 (R 1 = H) is believed to participate in a 1,3‐dipolar cycloaddition with the aryl aldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…For example, imine hydrolysis [50], epoxide ring opening [51], the Biginelli reaction [52], and dipolar cycloaddition [53] have already been performed under boronic acid catalysis. In 2008, Whiting et al reported a catalytic aldol reaction and condensation through in situ boron ate complex enolate generation in water (Scheme 17) [54]. The sodium ate complex 44 of benzimidazolylphenylboronic acid shows high catalytic activity in water at 20 mol% for the aldol reaction of aldehydes with hydroxyacetone in high conversion and moderate to high syn selectivity.…”
Section: Other B(iii)-catalyzed Reactionsmentioning
confidence: 98%
“…The pioneering use of aminoboronic acids was reported by Letsinger . Over the last 20 years, several direct amide formation and aldol reactions have been described involving aminoboronic acids as catalysts …”
Section: Introductionmentioning
confidence: 99%